(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The English language has a rich and fascinating history that spans over 1,400 years. From its earliest roots in Old English to its modern-day form, the English language has evolved and transformed over time, reflecting changes in society, culture, and technology. The study of language evolution is not only important for understanding the history of the English language, but also for understanding the world we live in today